SUSTAINABILITY OF INDONESIA TRADEMARK LAW AS UMBRELLA LAW IN RESOLVING DOMAIN NAMES DISPUTE IN INDONESIA - Ayup Suran Ningsih (Fakultas Hukum Universitas Gadjah Mada, 2020)
AbstractProtection regarding intellectual property in domain names becomes an important thing that must be considered by the domain name’s holder or user. Domain names are by character quite similar to trademarks since they serve as source indicators. This article is written to analyse the Suitability of Indonesia Trademarks Law as Umbrella Law in Resolving Domain Names Dispute in Indonesia. The methodology used in writing this article is normative legal research. Through the comprehensive discussion, it can be concluded that Indonesia trademark law is not suitable to resolve domain name dispute in Indonesia. A domain name is different from a mark based on Indonesia Trademark Law. IntisariPerlindungan terkait kekayaan intelektual dalam nama domain menjadi hal penting yang harus dipertimbangkan oleh pemegang atau pengguna nama domain. Nama domain secara karakter sangat mirip dengan merek dagang karena mereka berfungsi sebagai indikator sumber. Artikel ini bertujuan untuk menganalisis Kesesuaian Hukum Merek Dagang Indonesia sebagai Hukum Payung dalam Menyelesaikan Sengketa Nama Domain di Indonesia. Metodologi yang digunakan dalam penulisan artikel ini adalah penelitian hukum normatif. Melalui pembahasan yang komprehensif dapat disimpulkan bahwa hukum merek dagang Indonesia tidak cocok untuk menyelesaikan perselisihan nama domain di Indonesia. Nama domain berbeda dengan tanda yang diatur pada UU Merek Dagang Indonesia.